Réponses

2012-12-21T16:53:10+01:00

A = 2/(3/4) / (5/4 - 2/4) = 2/(3/4) = 2.4/3 = 8/3

B =\frac{21.10^{-4}.5.10^{8}}{7.10^{7}} = \frac{3.5.10^{4}}{10^{7}}=15.10^{4-7}= 15.10^{-3}=1,5.10^{-2} = 0,015

 

2012-12-21T16:59:24+01:00

Bonjour,

 

A = 3/4 + 5/4 : (5/4 -1/2 ) =

 

A = 8/4 : (5/4 -2/4 ) =

 

A = 8/4 : 3/4 =

 

A = 8/4*4/3 =

 

A = 8/3

 

 B=\frac {21*500*10^-^4*10^6*10^-^8}{0,7}=\frac {10500*10^-^6}{0,7}=15000*10^-^6=0,015 en  écriture décimale

 

B=1,5*10^-^2 en écriture scientifique

 

J'espère que tu as compris

a+